The role of cerium intercalation in the efficient dry exfoliation of graphene layers at a low temperature - Mehravar, S. (Elsevier Ltd, 2020)
Reduced graphene oxide (rGO) was efficiently exfoliated to a few-layer graphene by using Ce as an intercalant. Cerium was intercalated into graphene oxide by a co-reduction method to produce Ce-intercalated rGO. Fast exfoliation of the dried Ce-intercalated rGO was induced by heat treating it in an Ar atmosphere, at a specific temperature of 170 Â°C within 5 s. The exfoliation process was dependent on the drying method of the Ce-intercalated rGO. Morphological, crystallographic and surface chemical analyses of rGO, Ce-intercalated rGO and Ce-exfoliated graphene were analyzed by using field emission secondary electron microscopy (FE-SEM), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Fourier-transformed infrared spectroscopy (FTIR), N2 adsorption-desorption isotherm and X-ray diffraction (XRD), in order to elucidate the reaction mechanism involved in the present fast dry exfoliation. Due to its process simplicity, the exfoliation is scalable to produce larger quantity of few-layer graphene. Â© 2019 Elsevier B.V.